New species and new records of the genus Hexarhopalus Fairmaire, 1891 (Coleoptera: Tenebrionidae: Cnodalonini) from China - Ji, Quan-Yu; Ren, Guo-Dong; Bai, Xing-Long (Zootaxa, 2026)
Two new species of the subgenus Leprocaulus Fairmaire, 1896 within the genus Hexarhopalus Fairmaire, 1891 from China are described and figured: H. (L.) medogensis sp. nov. (Xizang), and H. (L.) umbratus sp. nov. (Yunnan). New records of its congeners are also given and figured: H. (L.) binhanus (Pic, 1922) and H. (L.) pacholatkoi Bečvář & Purchart, 2008 are reported as new to China (Yunnan); H. (L.) bisinuatus Ren & Xu, 2011 is reported from Chongqing and Guangxi for the first time; and H. (L.) nanlingensis Jiang, Li, Ji, Engel & Wang, 2021 is reported from Guangxi for the first time. All Chinese species of the subgenus Leprocaulus are keyed.